Telaah Faktor Sosial Demografi Terhadap Kesetujuan Masyarakat Pada Rencana Pengembangan Htr Di Kphp Gedong Wani - Wirna Ariani Pulungan; Samsul Bakri; Rudi Hilmanto (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Since 2007 the Ministry of Forestry rolling the policy on the use of community-based forest production through the Minister of Forestry (Minister) Number. P.23 / Menhut-II / 2007 dated June 25, 2007 on Procedures for Application Permit Utilization of Wood in Forest Plantation in Plantation Forest, which was later replaced by Regulation Nomor.P.55 / Menhut-II / 2011. HTR development policy is open access to the public to manage production forests legally. The aim of this study is to determine the influence of demographic factors socio-cultural factors and accessibility of the program Plantation Forests (demographic, social, cultural, property, accessibility). This research was conducted in the village of Sinar Rejeki, Karang Rejo village, Budi Lestari Village, and the village of Tanjung Bintang Subdistrict Tri Mulyo South Lampung regency in Lampung province in August 2014. This study has shown that the level of agreement of respondents to the Forest Plantation development plan Level of agreement of respondents to plan the development of Forest Plantation influenced significantly by group variable property: (a) the vehicle has 2.14 times greater odds than on who does not have (b) but that the procurement of dry land and wet land over an area of 1 ha of acceptability be 0,001 times. And group demographic variables, social, cultural and accessibility do not significantly affect the acceptability of Plantation Forest development plan. Keywords: community demographics, social factors, KPHP region